Urinary PSA: a potential useful marker when serum PSA is between 2.5 ng/mL and 10 ng/mL - Bolduc, Stéphane (Canadian Medical Association, 2007)
INTRODUCTION: Our objective was to evaluate the usefulness of urinary prostate specific antigen (PSA) in the differential diagnosis of benign prostatic hyperplasia (BPH) and prostate cancer. METHODS: We undertook a prospective study and obtained informed consent from 170 men. They provided blood samples to measure serum PSA and 50 mL of first-voided urine to measure urinary PSA. Seventy-seven men were diagnosed with BPH; 42 patients had newly diagnosed prostate cancer; and 51 were selected as age-matched control subjects. Data were analyzed using Wilcoxon signed rank tests, receiver operating characteristic (ROC) curves and logistic regression. RESULTS: Prostate volume was 35 cm(3) and 45 cm(3) (p < 0.05), serum PSA was 9.7 ng/mL and 4.5 ng/mL (p < 0.001) and PSA density was 0.28 and 0.11 (p < 0.01) for prostate cancer and BPH patients, respectively. Overall, urinary PSA was not significantly different, but PSA ratio (urinary:serum) was significantly different at 6.7 and 30.6 (p < 0.001) for prostate cancer and BPH patients, respectively. A subgroup with serum PSA between 2.5 ng/mL and 10.0 ng/mL was selected and urinary PSA was significant: 52.6 ng/mL (n = 29) and 123.2 ng/mL (n = 35) (p < 0.05) for prostate cancer and BPH patients, respectively. PSA ratios were also significant (p = 0.007). ROC curves identified a cutoff for urinary PSA at > 150 ng/mL, with a sensitivity of 92.5%. When comparing prostate cancer patients with age-matched control subjects, serum PSA, urinary PSA and PSA ratio were different (p = 0.004). CONCLUSION: Our study supports urinary PSA as a useful marker in the differential diagnosis of prostate cancer and BPH, especially when serum PSA is between 2.5 ng/mL and 10 ng/mL. Low urinary PSA and PSA ratios point toward prostate cancer. A urinary PSA threshold of > 150 ng/mL may be used to decrease the number of prostatic biopsies.